Spontaneous pregnancy in a patient with premature ovarian insufficiency after a failed attempt of ovulation induction - Yaacob, Nasuha; Adzlan, Fadzlin M.; Ab Rahman, Siti Nabillah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Premature ovarian insufficiency (POI) is defined as intermittent or permanent gonadal insufficiency before age of 40 years. POI causes female infertility hence pregnancies are uncommon but not impossible. Ovarian failure is not permanent, unlike menopause. There could be intermittent ovulation and spontaneous pregnancy. Many protocols aimed to restore ovarian functions have been described in the recent years. This is a case of POI women who conceived spontaneously in the immediate menstrual cycle after a failed attempt at ovarian stimulation following many years on hormone replacement therapy (HRT). She had an unremarkable pregnancy and delivered a healthy baby via caesarean section.